The dual role of autophagy in cancer stem cells: implications for tumor progression and therapy resistance - Haiqing Jia; Jing Wei; Wei Zheng; Zhuo Li (Journal of Translational Medicine)
Abstract Cancer stem cells (CSCs) constitute a small yet crucial subgroup in tumors, known for their capacity to self-renew, differentiate, and promote tumor growth, metastasis, and resistance to therapy. These characteristics position CSCs as significant factors in tumor recurrence and unfavorable clinical results, emphasizing their role as targets for therapy. Autophagy, an evolutionarily preserved cellular mechanism for degradation and recycling, has a complex function in cancer by aiding cell survival during stress and preserving balance by eliminating damaged organelles and proteins. Although autophagy can hinder tumor growth by reducing genomic instability, it also aids tumor advancement, particularly in harsh microenvironments, highlighting its dual characteristics. Recent research has highlighted the complex interactions between autophagy and CSCs, showing that autophagy governs CSC maintenance, boosts survival, and aids in resistance to chemotherapy and radiotherapy. On the other hand, in specific situations, autophagy may restrict CSC growth by increasing differentiation or inducing cell death. These intricate interactions offer both obstacles and possibilities for therapeutic intervention. Pharmacological modulation of autophagy, via inhibitors like chloroquine or by enhancing autophagy when advantageous, has demonstrated potential in making CSCs more responsive to standard treatments. Nonetheless, applying these strategies in clinical settings necessitates a better understanding of context-dependent autophagy dynamics and the discovery of dependable biomarkers indicating autophagic activity in CSCs. Progressing in this area might unveil novel, accurate strategies to tackle therapy resistance, lessen tumor recurrence, and ultimately enhance patient outcomes.